The SDGs and food system challenges: Global trends and scenarios toward 2030 - Martin, Will; Vos, Rob (International Food Policy Research Institute, 2024)
Progress toward reducing global hunger has stalled since the mid-2010s. In fact, hunger is on the rise again, driven by slowing economic growth and protracted conflict, intensified by the impacts of climate change and economic shocks in many low- and middle-income countries. In addition, food systems worldwide have suffered disruptions in recent years, caused by the COVID-19-related global recession and associated supply chain disruptions, and exacerbated by the war in Ukraine. These factors have also jeopardized efforts at addressing the challenges to food system sustainability. The 2030 Agenda for Sustainable Development and the related sustainable development goals (SDGs), defined in 2015, recognize these challenges and set ambitious targets to end hunger and all forms of malnutrition and to make agriculture and food systems sustainable by 2030. Many other fora have restated and reiterated these ambitions, including the 2021 United Nations Food System Summit (UNFSS). While governments around the world have subscribed to these ambitions, collectively they have not been very specific as to how to achieve the SDGs and related goals and targets, except for three means of implementation (MOI) involving (i) increases in research and development, (ii) reductions in trade distortions, and (iii) improved functioning and reduced volatility in food markets. This paper is part of a wider effort at assessing the international community’s follow-through on the above ambitions and the related (implicit or explicit) commitments made toward action for achieving them. While not presenting new research findings, we bring together available evidence and scenario analyses to assess the progress made toward the ambitions for transforming food systems, the actions taken in regard of the internationally concerted agenda, and the potential for accelerating progress. The number of hungry people in the world has risen from 564 million in 2015, when the SDGs were agreed, to 735 million in 2022. While declines to between 570 and 590 million by 2030 are projected, this is far above the 470 million projected in the absence of the COVID-19 pandemic and the Ukraine war. The share of the world’s people unable to afford healthy diets is projected to decline from 42 percent in 2021 to a still far too high 36 percent by 2030. On the means of implementation, levels of spending on agricultural research and development have increased, particularly in key developing countries such as Brazil, China and India. However, rates of investment remain too low for comfort, particularly in low-income countries. Also, little progress has been made in reducing agricultural trade distortions and many countries continue to use trade policy measures, such as export restrictions, which have proven to increase the volatility of both world and domestic food prices. We conclude that progress toward the SDG-2 targets has been dismal, and that the food system challenges have only become bigger. But we also find that it is not too late to accelerate progress and that the desired food system transformation can still be achieved over a reasonable timespan and at manageable incremental cost. Doing so will require unprecedented concerted and coherent action on multiple fronts, which may prove the biggest obstacle of all.